Analisis Kepuasan Konsumen Terhadap Produk Unggulan Lilin Aromaterapi Lavender: Studi Kasus : Natureline Boyolali - Nazla, Sofiyatun; Soebagiyo, Daryono (Universitas Muhammadiyah Surakarta, 2024)
This research aims to analyze consumers of Natureline Boyolali's superior products, to find out whether or not many consumers use Natureline's superior products. The sample in this research was collected by distributing questionnaires and getting 42 respondents, who were consumers of Natureline Boyolali. The results of this research show that Natureline is widely known and has quite high public demand for purchasing superior products. Aromatherapy is a preparation that contains ingredients with a particular smell and fragrance which can provide a relaxing effect by providing a sense of calm and relieving tension due to illness, work pressure, family problems and other social problems. Lavender uses linalyl acetate and linalool. Linalyl acetate and linalool do not have dangerous side effects for health. Natureline has good quality and can satisfy consumers. Consumer satisfaction is driven by several factors such as satisfaction with product durability, satisfaction with price which means the company has succeeded in setting competitive prices, as well as review of product quality meaning the company has succeeded in maintaining product quality as shown by the number of complaints from consumers.